Water Assessment in Kabul River Basin - Safi, Abdul Ghias (Journal of Natural Sciences – Kabul University, 2021)
Water is an essential element for the survival of all living organisms. Without water, life on Earth would cease to exist. Over recent decades, the availability of surface and groundwater has decreased significantly. Reduced water availability, combined with the threats of drought and flash floods, affects the lives of people, plant coverage, and the environment. Rapid population growth, climate change, and poor water management have adversely impacted water resources in the Kabul River Basin. This paper examines the Kabul River Basin's water flow and the effects of climate change on the region. It assesses water flow and precipitation patterns over several years, evaluates damage to infrastructure and property, and proposes solutions to address these challenges.